Towards a Class-Struggle Anthropology - Menzies, Charles; Marcus, Anthony (Anthropologica, 2022)
Dancing between review and argument this paper lays out a foundation for a class-struggle anthropology—that is, an anthropological practice that can be linked to the ultimate goal of achieving a classless society. To this end we will review those anthropologists who have gone before us, pulling out those works of theirs that we see as critical in (re)building a class-struggle anthropology. As part of this process we discuss the relationship between what has stood as Marxist anthropology in North America, the idea of socialism, the political development of the world working class during the nine decades since the October Revolution, and the challenges of intellectual continuity in the face of differing generational experiences of Marxist anthropologists. Ultimately we argue that a progressive anthropology necessarily involves political activism in our work, communities, and schools.